Model Customer Satisfaction And Customer Behaviour Intention In Improving The Dimension Of Referral Marketing, Experiental Marketing, Service Marketing (Economic and Bussiness Faculty, Dr Soetomo University, 2020)
This research aims to test and analyze customer satisfaction model and customer behaviour intention in meningkatkandimensireferral marketing, experientalMarketing, service marketing in customer user product PT. DenpooMandiri Indonesia Branch Surabayi have been respondents to the study as much as 130 people, consisting of 90 women and 40 men. This analysis uses the analysis path. Calculation of statistical analysis using SPSS aimed at calculating the significant or absence of a study. This research can contribute to the company PT. DenpooMandiri Indonesia in increasing customer satisfaction by combining the dimensions that will be researched and researchers want to help increase the sales level of Denpoo products so that the product can be felt by the customer. Findings of this research with statistical analysis calculations using SPSS Path analysis that aims to calculate the significant or absence of a study. Based on the results of the overall research of data analysis can be noted that empirically tested by Bersama–sama referral marketing variables, experiential marketing, service marketing, customer satisfaction has a significant impact to the customer behaviour intention. Customers will increase when referral marketing variables, experiental marketing, service Marketingcan be tested and can provide benefits to the community and employees of the company.